Examination of Conceptual Change Research Over A Decade: A Bibliometric Analysis Using Science Mapping Tool - Ananda Hafizhah Putri; Achmad Samsudin; Muhammad Guntur Purwanto; Andi Suhandi (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2022)
This study aims to deliver a summary of conceptual change research based on scientific production, most rele-vant researchers and countries, co-authorship collaboration, and research foci. A bibliometric analysis of the scientific output in the field of conceptual change was carried out utilizing articles published between 2012 and 2021.A total of 515 articles published in educational psychology, cognitive science and science education jour-nals were extracted from Scopus databases. The main findings reveal that the number of articles on conceptual change during the 2012-2021 period is relatively constant. Co-authorship collaborations predominantly consist of researchers from the same country. In addition, a shift in the research foci was observed. Past studies have been widely carried out across disciplines, such as educational psychology, cognitive science, and pedagogic. Meanwhile, recent research foci have brought up curriculum and curriculum development as important keywords.